Simulation of a frequency-reconfigurable multiband antenna for 5G and Wi‑Fi 6E/7 applications - Ismahane Refsi; Miloud Benchehima; Mohammed Hicham Hachemi; Salah Eddine Brezini (Institute of Advanced Engineering and Science, 2026)
This paper presents a compact frequency-reconfigurable multiband antenna design suitable for 5G and Wi‑Fi 6E/7 applications. Designed on a low-cost FR4 substrate, the antenna occupies a compact footprint of 28×15×1.6 mm, making it one of the smallest designs reported and suitable for integration into space-constrained devices. Its simple geometry enables easy design and integration across platforms. Frequency reconfigurability is achieved using PIN-diode-controlled reactive elements that manipulate current distribution to shift resonant frequencies. The design and optimization were performed using CST Microwave Studio to ensure accurate electromagnetic performance. Simulation results demonstrate that the proposed design supports up to eight distinct operating modes, highlighting its versatile frequency-reconfigurable capability. Among these modes, some achieve excellent performance at specific frequency bands including Wi‑Fi 6E/7 (2.4, 5 and 6 GHz) and 5G sub-6 GHz (3.5 GHz). These findings are confirmed with simulation results showing clearly that the antenna exhibits S_11 below –20 dB across the targeted frequency bands. The antenna also demonstrates satisfactory gain, with values above 1.5 dBi across the desired frequency bands. The antenna reveals a voltage standing wave ratio (VSWR) below 1.5 across the intended frequency bands. These characteristics make the proposed antenna a compact, versatile and efficient solution for current and future wireless communication systems.